2020
DOI: 10.1002/adem.202000193
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Tensile Deformation of High Strength Aluminum Alloys Processed Following Novel Thermomechanical Treatment Strategies

Abstract: Herein, the effects of a very recently introduced novel thermomechanical process route on the microstructural evolution and dynamic tensile deformation behavior of two different precipitation hardenable aluminum alloys, i.e., AA6082 and AA7075, are studied. The investigated materials are hot formed and quenched in differently tempered tools to reveal the influence of cooling rate. Microstructure analysis is conducted to study the influences of different cooling strategies on the microstructure evolution and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 94 publications
0
12
0
Order By: Relevance
“…Lower cooling rates after solution treatment favor the evolution of relatively large precipitates alongside the grain boundaries eventually leading to a reduction of precipitate forming elements in the surrounding areas [10,[36][37][38]. Therefore, the high strength of AA7075 alloy formed and cooled in the cold die can be attributed to the formation of fine and dispersed precipitates after the aging treatment [17,18].…”
Section: Conditions Yield Strength (Mpa) Ultimate Tensile Strength (Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower cooling rates after solution treatment favor the evolution of relatively large precipitates alongside the grain boundaries eventually leading to a reduction of precipitate forming elements in the surrounding areas [10,[36][37][38]. Therefore, the high strength of AA7075 alloy formed and cooled in the cold die can be attributed to the formation of fine and dispersed precipitates after the aging treatment [17,18].…”
Section: Conditions Yield Strength (Mpa) Ultimate Tensile Strength (Mmentioning
confidence: 99%
“…Forming limit curves (FLCs) for the hot forming of an aluminum alloy were also obtained in another study by designing a novel test device based on a commercial Gleeble machine [14]. The results of this preliminary research awaked the interest in hot stamping and thermo-mechanical processing of AA7075 alloy and entailed a high number of scientific and industrial studies [5,6,[16][17][18]. It was shown that hot stamping of AA7075 alloy, followed by an adequate artificial aging treatment, resulted in the production of components with mechanical properties similar to the T6 condition [6].…”
Section: Introductionmentioning
confidence: 97%
“…For both geometries, a gauge length of The same setup can be used for forming of other alloys such as aluminum alloys as well. [79] Reproduced with permission. [79] © 2020, WILEY-VCH Verlag GmbH.…”
Section: Characterization Of Properties and Local Deformation Behaviormentioning
confidence: 99%
“…[79] Reproduced with permission. [79] © 2020, WILEY-VCH Verlag GmbH. 100 mm was chosen and a minimal gauge width of 14 mm at a sheet thickness of 1.5 mm.…”
Section: Characterization Of Properties and Local Deformation Behaviormentioning
confidence: 99%
“…The main experimental setup in the present study consisted of a roller hearth furnace for solutionizing the sheet material and a hydraulic press (MAE DE Erkrath, Germany, 400 Z 160) with a press capacity of 4000 kN equipped with hat-shaped forming tools. For the artificial aging treatment, a chamber furnace (ThermConcept, Bremen, Germany, KM 710/13) was used to achieve a homogeneous temperature distribution (Figure 1a) [33,34].…”
Section: Experimental Setup and Programmentioning
confidence: 99%